Transient renal Fanconi syndrome in a Chihuahua exposed to Chinese chicken jerky treats - Hooijberg, E. H.; Furman, E.; Leidinger, J.; Brandstetter, D.; Hochleithner, C.; Sewell, A. C.; Leidinger, E.; Giger, U. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2015)
Transient Fanconi syndrome without azotemia was diagnosed in a dog and was associated with ingestion of Chinese chicken jerky treats. Fanconi syndrome is a proximal renal tubular defect and a diagnosis was made based upon severe glucosuria with normoglycemia, and severe generalized aminoaciduria. The clinical signs of polyuria and polydipsia as well as the massive urinary metabolic abnormalities resolved after jerky treat withdrawal. While frequently seen in North America and Australia, this is the first report of jerky treat induced Fanconi syndrome in continental Europe. Clinicians should be aware of this potential intoxication and be vigilant for a history of jerky treat consumption in a dog with glucosuria.
Keywords: Aminoaciduria; nephrotoxin; glucosuria; metabolic disease; nutrition